Enrichment of Omega-3 Fatty Acids using Urea Complexation Method to Enhance the Nutritive Value of Stingray Fish (Dasyatis Sephen F.) Liver Oil - Sathees, D.; Vidanarachchi, J.K.; Himali, S.M.C. (International Journal of Trend in Scientific Research and Development Journal, 2019)
Abstract : Lipid fraction extracted from tissues of oily fish and fishery by-products are one of the best source of omega-3 (?-3) polyunsaturated fatty acids (PUFAs), mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Method of oil extraction from the Dasyatis sephen liver is simple and cheap. Therefore, the present study was conducted to extract and enrich the Omega-3 fatty acids from Dasyatis sephen liver which is discarded during dry fish production. Bligh and Dyer’s method was used to extract oil. Fatty acids profiles were determined by Gas-Liquid Chromatography method (GLC). Average liver lipid recovery was 69.54 % (w/w). Crude liver oil fatty acid profile of DHA and EPA was 0.5% and 0.6%, respectively. Urea complexation was done to enrich the extracted Omega-3 fatty acids. Physio-chemical properties such as moisture content, color, specific gravity, peroxide value, and fatty acid compositions were obtained under the tolerable standard. The level of DHA:22:6n-3 and EPA: 20:5n-3 in the enriched Dasyatis sephen oil were 9.7 % and 8.7 %, respectively. It could be concluded that the converting of Ray fish by-product into enriched oil is an opportunity of adding value to the fish by-product and could be suitable for applications in pharmaceutical and nutraceutical industries.
Keywords: Fatty acid; Fish Oil; Ray Fish